Deliberate learning in corporate acquisitions: post‐acquisition strategies and integration capability in U.S. bank mergers - Zollo, Maurizio; Singh, Harbir (Strategic Management Journal, 2004)
Abstract This paper introduces a knowledge‐based view of corporate acquisitions and tests the post‐acquisition consequences on performance of integration decisions and capability‐building mechanisms. In our model, the acquiring firm decides both how much to integrate the acquired firm and the extent to which it replaces this firm's top management team. It can also learn to manage the post‐acquisition integration process by tacitly accumulating acquisition experience and explicitly codifying it in manuals, systems, and other acquisition‐specific tools. Using a sample of 228 acquisitions in the U.S. banking industry, we find that knowledge codification strongly and positively influences acquisition performance, while experience accumulation does not. Furthermore, increasing levels of post‐acquisition integration strengthen the positive effect of codification. Finally, the level of integration between the two merged firms significantly enhances performance, while replacing top managers in the acquired firm negatively impacts performance, all else being equal. Implications are drawn for both organizational learning theory and a knowledge‐based approach to corporate strategy research. Copyright © 2004 John Wiley & Sons, Ltd.